2017
DOI: 10.17352/2455-8400.000020
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Feeding Ecology and Prey Preference of Bagrid Catfish, Mystus tengara (Hamilton, 1822) in Low Saline Polyculture Ponds of Indian Sundarbans

Abstract: Growth performances, feeding ecology and prey preferences of Must us tengara (Hamilton, 1822) reared in low saline homestead traditional polyculture ponds in Sundarbans were studied for 12 months. Mixed carp early fi ngerlings (4.98±0.61 cm, 1.09±0.26 g) @ 14000 nos ha-1 and wild collected mixed bagrid catfi sh juveniles (5.09±0.48 cm, 1.38±0.11 g) including M. tengara were stocked @ 5000 juveniles ha-1. Farm yard manure @ 200 kgha-1 was applied monthly and household dining wastes (11.37±2.08 kgha-1day-1) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The results revealed that the final weight, weight gain, SGR, and survival were inversely related to stocking density. The present results coincide with the findings of (Mondal et al, 2017) who obtained the best growth in gulsha farming at lower stocking densities. The lowest stocking densities are expected to provide more space, food, and less competition (Ahamed et al, 2018).…”
Section: Growth Performances Of Tengra M Vittatus Under Polyculture F...supporting
confidence: 92%
See 1 more Smart Citation
“…The results revealed that the final weight, weight gain, SGR, and survival were inversely related to stocking density. The present results coincide with the findings of (Mondal et al, 2017) who obtained the best growth in gulsha farming at lower stocking densities. The lowest stocking densities are expected to provide more space, food, and less competition (Ahamed et al, 2018).…”
Section: Growth Performances Of Tengra M Vittatus Under Polyculture F...supporting
confidence: 92%
“…(Ahamed et al, 2018). Comprehensive scientific studies are documented on the monoculture of M. gulio, which is primarily grown in coastal waters, in tide-fed brackish water ponds (CIBA 2015;Hossain et al, 2018;Lal, Jaya, and Sherly 2016;Mondal and Mitra 2016;, polyculture with tilapia-Oreochromis niloticus, mullet-Rhinomugil corsula, climbing perch-Anabas testudineus and stinging catfish-Heteropneustes fossils (Hossain et al, 2019) Pabda were hardly attempted for polyculture in the greater northern region. To ensure proper utilization of seasonal ponds, the culture of short-cycle species should be introduced in the semiarid zone to enhance fish production.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier researchers had investigated different aspects such as reproductive biology [ 26 , 27 ], fecundity estimation [ 8 ], food and feeding habit [ 28 ], feeding ecology [ 29 , 30 ], and growth and prey preference [ 30 ] of Tengara in India and Bangladesh. Prior to our present study, few researchers had studied the length-weight relationships and condition factors of Tengara .…”
Section: Introductionmentioning
confidence: 99%
“…Natural food is necessary to support fisheries productivity (Hartati et al, 2017;Albertson et al, 2018;Pusey et al, 2020;Thoral et al, 2021), including in brackish water fish (Karna et al, 2014;Mondal and Chakravortty, 2015;Mondal and Mitra, 2016). The natural food of fish includes plankton, aquatic plants, small invertebrates, benthic fauna, detritus, and bacteria associated with detritus (Mendoza and Henkel, 2017;Andriyani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%